Development of the Medical Information System for the Treatment of Hepatitis B Virus - Seong-Ran Lee, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study is to develop a medical information system for the treatment of hepatitis B virus.The study surveyed 154 people who visited the internal medicine department of the general hospital from August 5, 2019 to October 21, 2019 in the C area. The data were surveyed and interviewed.. .The general characteristics of the subjects were used by chi-square test. The change in patient condition was analyzed as t-test following the application of the information system.The results of this study are as follows. First, it was found that eating sprout barley after applying the information system was significantly higher than before the system was applied(t=-4.16, p<.01).. Second, liver disease has decreased since the 6th day of application of information system applied information system. However, liver disease has been on the rise again since the 18th This paper means its influence by accepting a specific strategic performance approach. The findings from the study confirmed that this information system is effective.